Responses of the Electricity Sector in 120 Economies to the COVID-19 Pandemic - Saltane, Valentina (World Bank, Washington, DC, 2022)
This brief provides descriptive evidence of the operational and policy responses of the electricity sector in 120 economies to the early stages of the Coronavirus (COVID-19) pandemic. In addition, to assess the intensity of operational and regulatory actions taken in response to the pandemic, the Brief proposes a COVID-19 electricity sector response measure. This measure comprises seven equally weighted variables that capture either utilities’ or utility regulators’ responses to the pandemic as well as domestic lockdown measures. Data show that most utilities continued issuing new electricity connections for businesses amid the pandemic. In most cases, utilities that continued issuing new electricity connections despite national lockdowns were able to do so due to well-established electronic and automated processes. In general, maintenance works and planned outages continued during the onset of the pandemic, although with some delays and exceptions. Increasingly, delayed electricity payments and defaults became more prevalent, especially among developing economies. Hence, numerous utilities modifed tariff and payment schedules to provide economic relief to clients.